MENTAL HEALTH OF PRIMARY CARE PROFESSIONALS IN THE MUNICIPALITY OF CAUCAIA - CE - Medeiros Campos, Tainah (Health and Society, 2025)
Primary care professionals face a series of daily challenges that directly affect their emotional well-being. The Unified Health System (SUS) depends on its ability to provide accessible and continuous care to the population, making it essential to ensure that these workers maintain their mental health. However, various stressors, such as excessive workload, scarcity of resources, and high societal expectations, often contribute to the psychological distress of these professionals. These stressors can result in conditions such as chronic stress, burnout syndrome, anxiety, and depression, affecting both the individual and the work team as a whole. Furthermore, the quality of care provided to the community is directly related to the emotional health of these workers, as exhausted or emotionally compromised professionals tend to provide less empathetic and effective care. A cross-sectional study using the Maslach Burnout Inventory revealed that 10.6% of professionals were at high risk of burnout. The subscales showed that 29.8% had high emotional exhaustion, 52.1% had reduced professional fulfillment, and 22.3% had depersonalization. (Silva et al, 2023) This article therefore seeks not only to identify the factors that contribute to mental illness among primary care professionals but also to explore solutions that can be implemented to mitigate these impacts. The literature review and empirical data obtained through interviews with professionals working in the field highlight the urgent need for interventions that promote comprehensive care for these workers, considering their emotional and psychological needs.